Identification of novel biomarkers for anti-Toxoplasma gondii IgM detection and the potential application in rapid diagnostic fluorescent tests - Nguyen, Minh-Ngoc; Yeo, Seon-Ju; Park, Hyun (Frontiers in Microbiology, 2024)
Toxoplasmosis, while often asymptomatic and prevalent as a foodborne disease, poses a considerable mortality risk for immunocompromised individuals and during pregnancy. Point-ofcare serological tests that detect specific IgG and IgM in patient sera are critical for disease management under limited resources. Despite many efforts to replace the T.gondii total lysate antigens (TLA) by recombinant antigens (rAgs) in commercial kits, while IgG detection provides significant specificity and sensitivity, IgM detection remains comparatively low in sensitivity. In this study, we attempted to identify novel antigens targeting IgM in early infection, thereby,